Shallot Agribusiness Development Strategy in Purworejo Village, Malang District - Sri Hindarti; Lia Rohmatul Maula (Dwijendra University, 2020)
The development of shallots is needed in Malang Regency to reduce imports, which often occur. Therefore this research was conducted with the aim of identifying internal and external factors that influence shallot agribusiness, formulating development strategies, and determining the priority of shallot agribusiness development strategies. The research was determined in Purworejo Village as one of the largest shallot production centers in Malang Regency. The research method was carried out by interview and direct observation of farmers. Data analysis using IFE analysis, EFE, IE (Internal-External) matrix, SWOT matrix, and QSPM analysis. The results showed that the internal factors affecting shallot agribusiness were the skills and experiences of farmers as strengths and information and technology as weaknesses, while the external factors were market demand as an opportunity and distribution monopoly by large entrepreneurs as a threat. An appropriate strategy is an aggressive strategy (S-T), namely by utilizing strength to seize opportunities that exist in the form of local production input development.